Factors that Influence Internal Control Weakness of Local Government (Empirical Study on Provincial Government in Indonesia) - Arif Kurniawan Wahono; Lilik Purwanti (Jurnal Ilmiah Mahasiswa FEB, 2014)
This study aimed to test factors that influence internal control weakness of local government. Independent variables were economic growth was measured by gross domestic product regional, government size was measured by total assets, revenues of local government (PAD), complexity was measured by total population. Dependent variable was Internal control weakness was measured by the number of BPK RI’s finding about Internal Control Systems.  This study used secondary data from BPK RI report and BPS report. This study’s object was 33 provincial government in Indonesia with period 2012-2013, so number of samples were 66. Hypothesis tests used multiple regression analysist. F test showed economic growth, government size, PAD and complecity had simultaneous significant effect on the internal control weakness. T-test showed government size had partial significant effect on the internal control weakness. Economic growth, PAD and complexity didn’t have significant partial effect on internal control weakness.Keywords: Internal Control Weakness, Economic’s Growth, Government’s Size, PAD and Complexity